How much unity do you need? Systemic contestation in EU foreign and security cooperation. Issue 3 (3rd July 2021) - Maurer, Heidi; Wright, Nicholas
ABSTRACT: The Common Foreign & Security Policy (CFSP) is a transnational policy framework to deliver collective foreign policy and also to manage differences among member states. As such, it has always been dependent on their support. Since 2019, however, disagreement within this system is said to have reached a new level. Taking this political trend as our starting point, this article proposes a new, conceptual approach to understanding how contestation challenges the EU's foreign policy cooperation system. While the majority of research focuses on disagreements in decision-making, we argue for a broader conceptualisation – systemic contestation. Drawing on norm contestation scholarship, we argue that systemic contestation manifests itself in two ways: as passive contestation, when member states disengage from and fail to take ownership of CFSP initiatives and their implementation; and as tacit contestation, when they fail to act when faced with the need to safeguard the system. This approach accounts for the transgovernmental character of the CFSP; and the central role of member states within it. Finally, we contend that our conceptualisation of systemic contestation offers promising new avenues for empirical research to understand the "black box" of EU foreign policy cooperation.